A new objective titration procedure using Remotely Contactless Intelligent Sleep Monitoring System for the treatment of mandibular advancement device in OSAHS patient - Lei, Huijia; Zhu, Sixiang; Yang, Jing; Lai, Youqing; Wang, Zijing (Frontiers in Neurology, 2025)
BackgroundThe key to treating Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHS) by mandibular advancement device (MAD) lies in determining the optimal mandibular advancement, but current subjective titration methods are time-consuming and have poor compliance. Therefore, this study proposes an objective titration scheme based on a Remotely Contactless Intelligent Sleep Monitoring System (RCISMS) to optimize the MAD titration process, improve treatment efficiency, and enhance patient comfort.MethodsThis study enrolled 60 OSAHS patients, randomly divided into a RCISMS-guided titration group (n = 30) and a subjective titration group (n = 30). Patients in the RCISMS-guided titration group used RCISMS at home to monitor AHI, which was transmitted in real-time to clinicians online for remote guidance on MAD adjustments. The subjective titration group required adjustments based on patient self-reports during clinic visits. The primary endpoint was the reduction in AHI, and secondary endpoints included titration time efficiency and improvements in subjective symptoms (Epworth Sleepiness Scale, Snoring Scale).ResultsBoth RCISMS-guided and subjective titration significantly reduced AHI (by 73.7 and 69.0%, respectively), with no significant difference in final AHI levels between the two groups (p = 0.0828). RCISMS-guided titration significantly shortened the titration cycle (27.00 ± 2.12 days vs. 45.07 ± 8.25 days, p < 0.0001), saving 40.01% of the time compared to subjective titration. There were no significant differences between the two groups in ESS reduction (RCISMS group 3.0 ± 1.2 vs. subjective titration group 3.3 ± 1.5, p = 0.3943) and Snoring VAS scores reduction (RCISMS group 3.8 ± 0.5 vs. subjective titration group 3.9 ± 0.5, p = 0.3306).ConclusionThe RCISMS-guided MAD titration scheme can achieve the same therapeutic effect as traditional subjective titration methods in a shorter time, while reducing the number of patient visits, improving treatment convenience and compliance, and demonstrating significant potential for clinical application.